μCloud - Fouodji Tasse, Ghislain (Rhodes University, Faculty of Science, Department of Computer Science, 2012)
The advancements in virtualization technologies have provided a large spectrum of computational approaches. Dedicated computations can be run on private environments (virtual machines), created within the same computer. Through capable APIs, this functionality is leveraged for the service we wish to implement; a computer power service (CPS). We target peer-to-peer systems for this service, to exploit the potential of aggregating computing resources. The concept of a P2P network is mostly known for its expanded usage in distributed networks for sharing resources like content files or real-time data. This study adds computing power to the list of shared resources by describing a suitable service composition. Taking into account the dynamic nature of the platform, this CPS provision is achieved using a self stabilizing clustering algorithm. So, the resulting system of our research is based around a hierarchical P2P architecture and offers end-to-end consideration of resource provisioning and reliability. We named this system Î¼Cloud and characterizes it as a self-provisioning cloud service platform. It is designed, implemented and presented in this dissertation. Eventually, we assessed our work by showing that Î¼Cloud succeeds in providing user-centric services using a P2P computing unit. With this, we conclude that our system would be highly beneficial in both small and massively deployed environments.,KMBT_223,Adobe Acrobat 9.51 Paper Capture Plug-in
a P2P cloud platform for computing service provision
Keywords: Cloud computing; Peer-to-peer architecture (Computer networks); Computer architecture; Computer service industry